Faktor-Faktor yang Mempengaruhi Intention Whistleblowing - Upit Arapia Rahayu; Christina Dwi Astuti (SAFE-Network, 2023)
This study aims to determine the factors that influence whistleblowing intentions such as attitudes towards behavior, subjective norms, perceptions of behavioral control, perceptions of the seriousness of fraud, perceptions of threats of retaliation against whistleblowing intentions internally and externally and rationalization as moderation. The population in this study were employees who working in the accounting field in the Jabodetabek area which is primary data using a questionnaire survey and a purposive sampling method which has three criteria so that out of 278 respondents only 271 respondents could be sampled. This study uses multiple linear regression analysis tests. The results of this study are that attitudes towards behavior have a positive effect on whistleblowing intention internally, subjective norms have a positive effect on whistleblowing intention internally and externally, perceived behavioral control has a positive effect on whistleblowing intention externally, perceptions of seriousness fraud has a positive effect on whistleblowing intention internally, perceptions of the threat of retaliation have a negative effect on whistleblowing intention internally, rationalization is able to strengthen the effect of perceived seriousness of fraud on external whistleblowing intention, and rationalization is able to weaken perceptions of threats of retaliation on whistleblowing intention internally.